Non-invasive diagnosis of pulmonary hypertension: ESC/ERS guidelines with updated commentary of the Cologne Consensus Conference 2011 - Grünig, Ekkehard; Barner, Andreas; Bell, Michael; Claussen, Martin; Dandel, Michael; Dumitrescu, Daniel; Gorenflo, Matthias; Holt, Stephan; Kovacs, Gabor; Ley, Sebastian; Meyer, Joachim F.; Pabst, Stefan; et al. (International journal of cardiology, 2011)
The 2009 European Guidelines on Diagnosis and Treatment of Pulmonary Hypertension have been adopted for Germany. The guidelines contain detailed recommendations for the diagnosis of pulmonary hypertension. However, the practical implementation of the European Guidelines in Germany requires the consideration of several country-specific issues and already existing novel data. This requires a detailed commentary to the guidelines, and in some aspects an update already appears necessary. In June 2010, a Consensus Conference organized by the PH working groups of the German Society of Cardiology (DGK), the German Society of Respiratory Medicine (DGP) and the German Society of Pediatric Cardiology (DGPK) was held in Cologne, Germany. This conference aimed to solve practical and controversial issues surrounding the implementation of the European Guidelines in Germany. To this end, a number of working groups was initiated, one of which was specifically dedicated to the non-invasive diagnosis of pulmonary hypertension. This manuscript describes in detail the results and recommendations of the working group which were last updated in October 2011.
Available online 2 January 2012
Gesehen am 19.07.2022